Differential responses for stream algal assemblages exposed to factorial N and P enrichment along an in situ DOC gradient - Carrick, Hunter J.; Marble, Christine; Tian, Yong Q. (Frontiers in Environmental Science, 2023)
Nitrogen (N) and phosphorus (P) enrichment from the surrounding landscape can enhance the growth and abundance of algal assemblages. However, it is unclear how enhanced levels of dissolved organic carbon (DOC) might mediate the response of algae to nutrients. In this study, we aim to understand the relationship between N and P enrichment in stream reach with varying levels of DOC within a common watershed. Both suspended and benthic algal assemblages were exposed to increasing (low, moderate, high) levels of N and P in an in situ 3x3 factorial experimental design; these experiments were carried out simultaneously at three sites of varying DOC concentration. Results our experiments showed that both assemblages responded very differently to enrichment. For suspended algae, biomass was enhanced following enrichment with both N and P singularly and in combination, particularly at the highest concentrations levels for both nutrients (3-way ANOVA interactions; p < 0.05). This pattern was consistent at all levels of DOC at the three sites (3-way ANOVA Nutrient-site interaction; F=1.4, p=0.228). In contrast, benthic algal biomass progressively increased with enhanced concentration of both N and P, but only at the lowest level of DOC (3-way ANOVA site term; F=84.2, p=0.0001). No appreciable growth was observed under moderate or high DOC conditions and this pattern was likely attributed to low light penetration at these two sites (ANOVA). Our results indicate that eutrophication is likely to manifest itself in a complex manner throughout watersheds where loading of N and P interacts with DOC.